2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-0573
|View full text |Cite
|
Sign up to set email alerts
|

Micro Air Vehicle Scale Gust-Wing Interaction in a Wind Tunnel

Abstract: Andre for being a source of insight from people who have "been there". And to Jonathan and Hulya for helping me survive classes and keeping me sane. And a final thanks to my family and friends outside of the University for their support. With a special thanks to my fiancé, Caitlyn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Flow characterization results from Smith 6 showed that the jet from the gust inlet bent in the freestream direction, effectively causing a blockage effect, which accelerated the flow upward. This effect generated a gust magnitude, V/U∞, of greater than 35%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flow characterization results from Smith 6 showed that the jet from the gust inlet bent in the freestream direction, effectively causing a blockage effect, which accelerated the flow upward. This effect generated a gust magnitude, V/U∞, of greater than 35%.…”
Section: Resultsmentioning
confidence: 99%
“…1. The design of the gust generate was highly detailed in Smith et al 5 and Smith 6 . The gust generator was characterized using PIV for its effectiveness in changing the flow angle at a wing model location in the tunnel.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While computational fluid dynamics (CFD) studies of gust interactions are not uncommon [3][4][5] , they are seldom thoroughly compared to experimental results under different gusty conditions; and results on gust mitigation with flapping wings are limited. In our recent studies [6][7][8] , a comparison of gust wing interaction simulated experimentally with a vertical gust generator in a wind tunnel environment and numerically with advanced unsteady CFD tools has been carried out. Experimental results from Smith et al 7,8 are used to develop inlet and boundary conditions of a CFD model of the experimental setup 8 .…”
Section: Introductionmentioning
confidence: 99%